Efficacy and safety of antibody-drug conjugate combination therapy in advanced urothelial carcinoma - Jaime-Casas, Salvador; Barragan-Carrillo, Regina; Zugman, Miguel; Shah, Koral; Ebrahimi, Hedyeh; Mercier, Benjamin; Castro, Daniela V.; Zang, Peter D.; LeVee, Alexis; Yip, Wesley; Li, Xiaochen; Dizman, Nazli; et al. (Frontiers in Oncology, 2025)
Antibody-drug conjugates (ADCs) are revolutionizing the treatment landscape of advanced urothelial carcinoma (aUC). We systematically reviewed the PubMed and Embase databases for published clinical trials evaluating ADC-combination regimens in aUC. We extracted safety and efficacy outcomes, including objective-response rate (ORR), adverse events (AEs), and ≥ grade 3 AEs. We excluded narrative reviews, retrospective studies, and case reports. Two independent reviewers screened titles and abstracts for relevance, followed by a full-text review for eligibility. A total of 645 patients from 5 trials investigating anti-nectin-4 (enfortumab vedotin, EV), anti-TROP2 (sacituzumab govitecan, SG), and anti-HER2 (disitamab vedotin, DV) ADCs were identified. We recorded a pooled ORR of 65%. We recorded a pooled risk rate for all-grade toxicity of 57%. The most prevalent any-grade AEs were peripheral sensory neuropathy 52% (95% CI, 45%-59%), fatigue 45% (95% CI, 28%-64%), and diarrhea 42% (95% CI, 16%-74%). Peripheral sensory neuropathy, fatigue, and alopecia were more commonly observed in anti-nectin-4 regimens. Gastrointestinal (diarrhea and nausea) and hematologic (anemia and neutropenia) toxicities were more commonly observed in anti-TROP2 regimens. Hepatotoxicity was predominantly found in anti-HER2 regimens. While ADC-based combination regimens show promising responses, they also have high rates of AEs in patients with aUC.